Exploring the psychological sequelae of women who have undergone abortion : a multiple case-study approach - Tsilo, Mildred Madithole (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Psychology))--University of Stellenbosch, 2007.